CLINICAL PHARMACEUTICAL EDUCATION AND CLINICAL PHARMACIST COMPETENCIES - Tashtanbekova , Ch; Shakirova, A (Uzbekistan Open Conference, 2025)
The article presents an overview of the development of clinical pharmaceutical education and clinical pharmacy in developed countries, and the main competencies of a clinical pharmacist as the main specialist in the rational use of drugs.
Keywords: clinical pharmacy; clinical pharmaceutical education; rational use of medicines